2002
DOI: 10.1159/000066483
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and the Growth Hormone-Insulin-Like Growth Factor Axis

Abstract: Osteoporosis is the result of an imbalance between bone resorption and bone formation. Currently, mainly drugs that inhibit bone resorption are available for the treatment of osteoporosis. A new approach in the treatment of osteoporosis is the use of anabolic agents that increase bone turnover, both bone formation and resorption. Growth hormone (GH) and insulin-like growth factors (IGFs) are essential in the development and growth of the skeleton and for the maintenance of bone mass and density. We will review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
3
26
0
3
Order By: Relevance
“…IGFs play also an important role in bone remodeling. Low-serum IGF levels decrease osteoblast proliferation and bone matrix formation and reduce the activation of osteoclasts (29). Several studies have demonstrated a positive correlation between the BMD of the lumbar spine and the IGF-I concentration (30).…”
Section: Acquired Factorsmentioning
confidence: 99%
“…IGFs play also an important role in bone remodeling. Low-serum IGF levels decrease osteoblast proliferation and bone matrix formation and reduce the activation of osteoclasts (29). Several studies have demonstrated a positive correlation between the BMD of the lumbar spine and the IGF-I concentration (30).…”
Section: Acquired Factorsmentioning
confidence: 99%
“…Normal mammalian aging is characterized by reduced potency in the GH/IGF-1 axis. Reduction in IGF-1 levels with age is directly linked to atrophy of bone, skeletal muscle, cardiac muscle, and other tissues displaying pathological aging (Adamo and Farrar, 2006;Anversa, 2005;Ceda et al, 2005;Geusens and Boonen, 2002). Exogenous administration of GH to aged individuals improves body composition, fitness, bone density, and other biological markers, albeit with some side effects .…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 plays an important role in bone remodelling. Low serum IGF levels decrease osteoblast proliferation and bone matrix formation and reduce the activation of osteoclasts (64). A positive correlation between BMD at the lumbar spine and IGF-1 concentration has been detected (48,65).…”
Section: Gh-igf-1 Axismentioning
confidence: 88%